Impact of Freezing Delay Time on Tissue Samples for Metabolomic Studies - Haukaas, Tonje H.; Moestue, Siver A.; Vettukattil, Riyas; Sitter, Beathe; Lamichhane, Santosh; Segura, Remedios; Giskeødegård, Guro F.; Bathen, Tone F. (Frontiers in Oncology, 2016)
Introduction: Metabolic profiling of intact tumor tissue by high resolution magic angle spinning (HR MAS) MR spectroscopy (MRS) provides important biological information possibly useful for clinical diagnosis and development of novel treatment strategies. However, generation of high-quality data requires that sample handling from surgical resection until analysis is performed using systematically validated procedures. In this study, we investigated the effect of post-surgical freezing delay time on global metabolic profiles and stability of individual metabolites in intact tumor tissue. Materials and methods: Tumor tissue samples collected from two patient derived breast cancer xenograft models (n=3 for each model) were divided into pieces that were snap-frozen in liquid nitrogen at 0, 15, 30, 60, 90, and 120 minutes after surgical removal. In addition, one sample was analysed immediately, representing the metabolic profile of fresh tissue exposed neither to liquid nitrogen nor to room temperature. We also evaluated the metabolic effect of prolonged spinning during the HR MAS experiments in biopsies from breast cancer patiens (n=14). All samples were analyzed by proton HR MAS MRS on a Bruker Avance DRX600 spectrometer, and changes in metabolic profiles were evaluated using multivariate analysis and linear mixed modeling (LMM). Results: Multivariate analysis showed that the metabolic differences between the two breast cancer models were more prominent than variation caused by freezing delay time. No significant changes in levels of individual metabolites were observed in samples frozen within 30 minutes of resection. After this time point, levels of choline increased whereas ascorbate, creatine and glutathione (GS) levels decreased. Freezing had a significant effect on several metabolites, but is an essential procedure for research and biobank purposes. Furthermore, four metabolites (glucose, glycine, glycerophosphocholine and choline) were affected by prolonged HR MAS experiment time possibly caused by physical release of metabolites caused by spinning or due to structural degradation processes. Conclusion: The MR metabolic profiles of tumor samples are reproducible and robust to variation in post-surgical freezing delay up to 30 minutes.